Simplified Heat Transfer Model for Spiral‐Coil Energy Pile Groups and the Pile–Pile Thermal Interference - Wang Dai; Shi Gang; Wang Song; Cai Hanshen (Energy Science & Engineering)
ABSTRACT The spiral heat exchanger of the energy pile groups is divided into multiple segments. Each heat exchanger segment is regarded as a three‐dimensional spiral heat source of finite length. Based on the segmental superposition method of time and space, a variable heat flow segmental superposition heat transfer model of spiral buried‐pipe energy pile groups considering the heat transfer between circulating water and energy pile is derived and established. The correctness of the simplified heat transfer model in this paper is verified by comparing its results with those of a COMSOL finite element model. Additionally, a simplified heat transfer model is used to study the thermal interference of energy pile groups. The results show that with the increase in working time, the thermal interference between energy pile groups increases gradually. The pile spacing s and pile diameter d have a significant effect on the thermal interference between energy pile groups: the smaller the pile spacing and pile diameter, the stronger is the thermal interference between energy pile groups. The pile length has a negligible effect on the thermal interference between energy pile groups. The larger the number of energy pile groups, the stronger is the thermal interference between energy pile groups. The thermal interference of an energy pile is related to its position in the pile groups. The thermal interference of the central pile is the largest. This is followed by the edge pile and then the corner pile. Considering the thermal shielding effect of energy piles, only the influence of adjacent piles should be considered when analyzing the thermal interference of energy piles. In addition, the pitch of the spiral heat exchanger and the flow rate of the circulating water have negligible effects on the thermal interference between energy piles. The operation mode of energy pile groups has a significant effect on the thermal interference between energy piles. The thermal interference of energy pile groups in the intermittent operation mode is stronger than that in the continuous operation mode. The shorter the intermittent time, the more intense is the thermal interference of energy piles. These factors should be considered in engineering design.